Efektifitas Hukum Adat Desa Kedis dalam Pelestarian Kesakralan Budaya Tari Rejang Keraman - Wijaya, Hendra; Wedha, Yogi Yasa; Wira Udytama, I Wayan Wahyu; Rosiana, Febe; Santoso Ratu, Dennis (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 1 (2025)DO - 10.24843/JMHU.2025.v14.i01.p08, 2025)
This discussion examines the role of customary law in preserving Rejang Keraman Dance in Kedis Village, Buleleng, Bali, amid the influence of globalization. The aim is to understand how customary law is able to maintain this tradition from the threat of modernization. this article uses a qualitative juridical emperis method with a legal anthropology approach. Data were collected through in-depth interviews with traditional leaders, direct observation of the ceremony, as well as a review of related literature. The results of this discussion show that customary law functions as an effective mechanism in maintaining the sacredness and preservation of Rejang Keraman Dance, by involving the entire village community. The conclusion of this discussion is that customary law in Kedis Village does not only function as a formal rule, but also as a means of protecting culture and social identity that can withstand the pressures of globalization. This discussion provides important insights for the development of customary law-based cultural preservation policies. Pembahasan ini mengkaji peran hukum adat dalam melestarikan Tari Rejang Keraman di Desa Kedis, Buleleng, Bali, di tengah pengaruh globalisasi. Tujuannya adalah untuk memahami bagaimana hukum adat mampu menjaga tradisi ini dari ancaman modernisasi. artikel ini menggunakan metode kualitatif yuridis emperis dengan pendekatan antropologi hukum. Data dikumpulkan melalui wawancara mendalam dengan tokoh adat, pengamatan langsung upacara, serta tinjauan literatur terkait. Hasil pembahasan ini menunjukkan bahwa hukum adat berfungsi sebagai mekanisme efektif dalam menjaga kesakralan dan kelestarian Tari Rejang Keraman, dengan melibatkan seluruh komunitas desa. Kesimpulan dari pembahasan ini adalah bahwa hukum adat di Desa Kedis tidak hanya berfungsi sebagai aturan formal, tetapi juga sebagai alat pelindung budaya dan identitas sosial yang mampu bertahan menghadapi tekanan globalisasi. Pembahasan ini memberikan wawasan penting untuk pengembangan kebijakan pelestarian budaya berbasis hukum adat.